Pengembangan Media Pop Up Book Pada Pembelajaran Ilmu Pengetahuan Sosial Materi Keberagaman Budaya Bangsaku di Kelas IV SDN Bangkingan II/ 442 Surabaya - Grashella Devanda Yulisma Putri; Yudha Popiyanto; Desi Eka Pratiwi (Institut Nalanda, 2023)
Learning media is a tool that is used as an intermediary from the teacher to students which contains material to achieve learning objectives. The research used in this study is research and development (Research and Development). The model used in this research is ADDIE (Anlysis, Design, Development, Implementation, Evaluation). The purpose of this research is to produce a Pop up book media that is suitable for learning activities in class IV SDN Bangkingan II/442 Surabaya. The instruments used in collecting data were validation test questionnaires for media experts, material experts, audience and pre-test, post-test questions. After conducting research by conveying material through Pop up book media, it increased through the post-test scores, which experienced an increase in the average score of 80-100 for each student.